2018
DOI: 10.1056/nejmoa1714719
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cardiac Screening in Adolescent Soccer Players

Abstract: Diseases that are associated with sudden cardiac death were identified in 0.38% of adolescent soccer players in a cohort that underwent cardiovascular screening. The incidence of sudden cardiac death was 1 per 14,794 person-years, or 6.8 per 100,000 athletes; most of these deaths were due to cardiomyopathies that had not been detected on screening. (Funded by the English Football Association and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
154
4
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(177 citation statements)
references
References 41 publications
10
154
4
9
Order By: Relevance
“…3 Previous studies addressing the incremental role of echocardiography in addition to history, physical examination and resting ECG failed to demonstrate a significant impact of this imaging modality. [4][5][6][7] Instead, prior investigations suggested that EST could substantially increase the diagnostic yield of PPE. [29][30][31] Sofi et al evaluated 30,065 individuals undergoing PPE and found that abnormalities at EST (including supraventricular arrhythmias or VA, ST-segment changes and intraventricular conduction disorders) allowed for the identification of a potentially fatal cardiac disorder in 56 participants with normal ECG (0.18%).…”
Section: Implications Of Adding Stress Testing To the Ppe Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Previous studies addressing the incremental role of echocardiography in addition to history, physical examination and resting ECG failed to demonstrate a significant impact of this imaging modality. [4][5][6][7] Instead, prior investigations suggested that EST could substantially increase the diagnostic yield of PPE. [29][30][31] Sofi et al evaluated 30,065 individuals undergoing PPE and found that abnormalities at EST (including supraventricular arrhythmias or VA, ST-segment changes and intraventricular conduction disorders) allowed for the identification of a potentially fatal cardiac disorder in 56 participants with normal ECG (0.18%).…”
Section: Implications Of Adding Stress Testing To the Ppe Protocolmentioning
confidence: 99%
“…3 Moreover, standard echocardiographic examination demonstrated little additional value for the identification of these concealed conditions. [4][5][6][7] According to the 1982 Italian law, the PPE protocol includes a constant-load ECG stress test (EST; modified Montoye step test), in addition to history, physical examination and resting ECG. Originally, the aim of EST was to assess the cardiological fitness for sports activity by evaluating the 'immediate recovery index' (IRI), based on the heart rate from the third to the fifth minute of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of modern ECG interpretation standards is likely to improve ECG's accuracy [5], the substantial number of false-positive findings among athletes leading to further investigations has prompted concerns regarding the costeffectiveness of universal ECG screening [6]. On the other hand, sensitivity of screening to detect subclinical cardiomyopathies is still suboptimal with some false-negative results, as demonstrated in a recent study among adolescent soccer players, in which most athletes who experienced SCD during the follow-up didn't have detectable abnormalities in the comprehensive screening [7].…”
mentioning
confidence: 99%
“…One-off cardiac screening at age 16 failed to detect most cardiomyopathies associated with sudden cardiac deaths in adolescent footballers, a large UK cohort study has found 1. But results from the 20 year study also showed that the rate of sudden cardiac deaths was much higher than expected, prompting the English Football Association (FA) to recommend more frequent cardiac assessments for young footballers.…”
mentioning
confidence: 99%
“…The screening results, reported in the New England Journal of Medicine ,1 showed that 42 athletes (0.38%) had cardiac disorders associated with sudden cardiac death, five of whom (0.04%) had hypertrophic cardiomyopathy.…”
mentioning
confidence: 99%